(untitled) (Transactions on Additive Manufacturing Meets Medicine, 2020)
Antimicrobial study was conducted to test the surfaces of additively manufactured (AM) polyamide parts via powder-bed fusion. As printed parts exhibit rough, porous and powdery surfaces providing a favorable breeding ground for bacteria and fungi. This creates an issue for AM parts intended for use in medical and other highly controlled applications. A novel surface processing method able to seal and smooth surfaces was used to improve antimicrobial properties of parts. Processed parts were tested for microbial growth and the results were compared to the unprocessed parts. This study presents the obtained results and discusses possible applications of this method.